p,p′-DDE activates CatSper and compromises human sperm function at environmentally relevant concentrations - Tavares, Renata S. (2013)
This work was supported by the Portuguese National Science Foundation (FCT) through a grant attributed to the CNC Institution (PEst-C/ SAU/LA0001/2011) and a Wellcome Trust Grant #86470 provided to S.J.P. and C.L.R.B. S.M. was supported by the Infertility Research Trust. R.S.T. is the recipient of a PhD fellowship from FCT (SFRH/ BD/46002/2008).